1990
DOI: 10.1128/aac.34.6.1041
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparative study of cefixime versus cephalexin in acute bacterial exacerbations of chronic bronchitis

Abstract: Patients with purulent exacerbation of chronic bronchitis were randomized to receive either a single 400-mg daily dose of cefixime or 250 mg of cephalexin, orally, four times a day. In a population of patients with chronic bronchitis, acute bacterial exacerbations of bronchitis are frequently seen (4). Such exacerbations often cause worsening of other comorbid conditions and contribute to hospitalization and indirectly to death. Although there has been debate about the need for and the efficacy of antimicrobia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…It is difficult to estimate the proportion of exacerbations which are due to M. catarrhalis. However, one study performed in a Veterans Administration facility found that 30% of exacerbations were caused by M. catarrhalis (328). In our prospective study of patients with COPD, M. catarrhalis is the second most common cause of exacerbations after nontypeable H. influenzae (unpublished observations).…”
Section: Immune Response (I) Interpreting the Literature Human Antimentioning
confidence: 88%
“…It is difficult to estimate the proportion of exacerbations which are due to M. catarrhalis. However, one study performed in a Veterans Administration facility found that 30% of exacerbations were caused by M. catarrhalis (328). In our prospective study of patients with COPD, M. catarrhalis is the second most common cause of exacerbations after nontypeable H. influenzae (unpublished observations).…”
Section: Immune Response (I) Interpreting the Literature Human Antimentioning
confidence: 88%
“…In our hospital, between 1994 and 2001 the main bacterial etiological agents isolated from middle ear fluids of children were Haemophilus influenzae (45%) and Streptococcus pneumoniae (39%); the percentages of these organisms remained almost constant during this period, whereas the incidence of M. catarrhalis increased from 4 to 11%. In adults, M. catarrhalis is one of the etiological agents of recurrent infections, particularly in patients with chronic obstructive pulmonary disease, and is responsible for approximately 30% of the new cases (37). The clinical management of patients infected with M. catarrhalis also is a problem, since high costs are associated with established therapies and there is global emergence of antibiotic-resistant strains (35).…”
mentioning
confidence: 99%
“…A Gram-stained sputum sample which shows a predominance of gram-negative diplococci is highly predictive for the presence of B. catarrhalis (80,128,170,175,185). Indeed, this is the single most useful diagnostic test in establishing B. catarrhalis lower respiratory tract infection.…”
Section: Lower Respiratory Tract Infectionmentioning
confidence: 99%